Pulse oximeter perfusion index as a new predictor of hypotension following subarachnoid block in lower segment Cesarean section: A prospective randomized study - Ashish Mohan M; Suman Gupta; Kavya Kanjikkal; Vankudoth Bhaskar (Asian Journal of Medical Sciences)
Background: Hypotension is a common adverse effect of spinal anesthesia, especially during pregnancy, due to the blockade of pre-ganglionic sympathetic fibers, resulting in reduced peripheral vascular resistance. This study explores the perfusion index (PI) as a potential predictor for hypotension during spinal anesthesia in lower segment Cesarean sections (LSCS).